The Curse Of Natural Resources In The Transition Economies - Tobias Kronenberg (Osteuropa-Institut München, 2002)
The curse of natural resources is a well-documented phenomenon in developing countries: Economies that are richly endowed with natural resources tend to grow slowly. Among the transition economies of the former “Eastern Bloc”, a similar pattern can be observed. In the first years of transition, output fell in all the former communist countries, but the Central European countries, which are rather poorly endowed with natural resources, recovered quickly and have enjoyed rather strong economic growth thereafter. The oil-rich economies of Eastern Europe and Asia have been less successful. This paper shows that a large part of the variation in growth rates among the transition economies can be attributed to the curse of natural resources. After controlling for numerous other factors, there is still a strong negative correlation between natural resource abundance and economic growth. Among the transition economies the prime reason for the curse of natural resource is corruption. The revenues from natural resource abundance induce rent-seeking behaviour and corruption across the bureaucracy and the business elite. This increased corruption slows down economic growth. Other reasons for the curse of natural resources may be Dutch disease effect and a neglect of education, but the evidence is not very strong. These findings stress the importance of fighting corruption, especially in natural resource abundant countries. An efficient bureaucracy is a necessary requirement for sustained economic growth. Investment in education is also crucial, but more in the long run. Economic policies that promote export growth, especially in the manufacturing sector, may also raise growth.
Keywords: 330; Rohstoffreichtum; Übergangswirtschaft; Rent-Seeking; Korruption; Schätzung; Osteuropa